Velocidade de movimento no desempenho muscular em mulheres jovens e idosas treinadas - Ceccato, Marilia [UNESP] (2013)
The aging process and/or associated factors cause changes in the musculoskeletal system, leading to sarcopenia and consequent reductions in muscle strength. However, the resistance training (RT) is a great strategy in the promotion and maintenance of health and improvement and/or maintenance of different expressions of muscle strength. Among the variables, the movement velocity (MV) has an important role in acute and chronic responses to RT. Objectives: Two studies were conducted with trained women, with the following objectives: Study 1 - analyze the acute effect of age and different MV on muscle performance; Study 2 - analyze the effect of age and eight weeks of RT, with different MV, on muscle performance. Methods: Thirteen young (22.0 ± 3.2 years) and 13 old women (65.6 ± 3.3 years), with experience in RT, participated. In Study 1 participants performed a control condition and two exercise conditions (intensity of 100% of 13-15 maximum repetitions - RM), carried out with two different VM (fast - 1:2 s; slow - 1,5:3 s), in the leg press machine. The muscle activation (EMG), isometric maximum voluntary contraction (MVC) and rate of force development (TDF and TDFPico) were measured before and after both conditions, and the number of repetitions, volume and VM were recorded during the exercise sessions. In study 2, participants performed eight weeks of RT with an intensity of 80% of 13-15 RM, in leg press machine, distributed according to two MV (slow group – 1.5: 3s; fast group - 1:2s). EMG, MVC, RFD and peak RFD were also evaluated in pre and post-trial period, also in the leg press. The MV were controlled by metronome with audible and visual signals. Results and Conclusion: In study 1, elderly decreased the number of repetitions in both experimental conditions (fast and slow MV), while young people demonstrated maintenance. Both groups showed a higher number of repetitions and volume in the faster MV condition when compared...